Characteristics of injuries during the 2006 Lebanon conflict: a three-center retrospective study of survivors, 16 years after the conflict - Farhat, Theresa; Nahouli, Hasan; Hajjar, Marwan; Abdul-Sater, Zahi; Kobeissi, Elsa; Menassa, Marilyne; Chaya, Bachar F.; Elamine, Ahmad; El Sheikh, Walaa G.; Tamim, Hani; Hettiaratchy, Shehan; Abu-Sittah, Ghassan (Frontiers in Public Health, 2024)
Background: Armed conflict injuries are a growing public health concern, particularly in regions like the Middle East and North Africa (MENA). The protracted conflicts and political unrest in this region have led to a substantial number of injuries. Despite this, there is still a limited understanding of the specific injury patterns stemming from conflicts, such as the 2006 Lebanon conflict. This study aimed to assess the characteristics and burdens of injuries resulting from this conflict, which occurred 16 years prior to this research.Methods: This retrospective study analyzed data of individuals affected by the 2006 Lebanon conflict, across three tertiary care centers. Demographics, injuries, complications, injury management, and hospitalization expenses were extracted from medical records and analyzed using SPSS version 29.0. Categorical variables were presented as counts and proportions, and continuous variables as mean ± standard deviation (SD). Hospital comparisons utilized chi-square or Fisher's exact tests for categorical variables, and one-way ANOVAs for continuous variables.Analysis was conducted from September to November 2023.Results: Across three hospitals, 341 patients were studied, comprising 73.6% males and 26.4% females. Among them, a notable proportion (57.3% males and 34.1% females) fell within the 18-39 age range. Children and adolescents under 18 years accounted for 15.9% of males and 25.9% of females. Blast-related injuries predominated, with 24.5% resulting from direct damage caused by explosive parts and 33.3% from blast wave forces. Extremity trauma occurred in 49.0% of patients, and head/neck trauma in 24.9%.Common injuries, including penetrating, musculoskeletal, and traumatic brain injuries affected 34.9%, 31.1, and 10.0% of patients, respectively. Wound repair, fracture treatment, and debridement were the most performed procedures on 15.5%, 13.5% and 9.7% of the patients, respectively. The total cost of care was USD 692,711, largely covered by the Ministry of Public Health (95.9%).Conclusions: Conflict-related injuries significantly contribute to the global burden of disease.Therefore, there is a pressing need to improve national guidelines to prioritize life-threatening cases and potential long-term disabilities. Furthermore, enhancing electronic registry systems to collect clinical data on injured patients is essential for conducting research and better understanding the needs of conflict casualties.